2011
DOI: 10.1007/s10237-011-0347-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of micro-CT-based finite element analysis to accurately quantify peri-implant bone strains: a validation in rat tibiae

Abstract: Although research has been addressed at investigating the effect of specific loading regimes on bone response around the implant, a precise quantitative understanding of the local mechanical response close to the implant site is still lacking. This study was aimed at validating micro-CT-based finite element (µFE) models to assess tissue strains after implant placement in a rat tibia. Small implants were inserted at the medio-proximal site of 8 rat tibiae. The limbs were subjected to axial compression loading; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Instead they were used to validate established micro-finite element models, providing a three-dimensional quantification of the strain throughout the whole tibiae [19,20]. We estimated maximum tensile strains at 25 per cent of the tibia length (hence corresponding to the strain gauge position and alignment) of approximately 260 m strain for the implanted tibiae subjected to 10 N loading.…”
Section: Quantification Of Peri-implant Bone Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead they were used to validate established micro-finite element models, providing a three-dimensional quantification of the strain throughout the whole tibiae [19,20]. We estimated maximum tensile strains at 25 per cent of the tibia length (hence corresponding to the strain gauge position and alignment) of approximately 260 m strain for the implanted tibiae subjected to 10 N loading.…”
Section: Quantification Of Peri-implant Bone Strainsmentioning
confidence: 99%
“…Bone strains measured on eight excised rat hindlimbs before and after implant placement [19,20] were used to establish the relationship between the applied load and the resulting bone strain. In short, a single element strain gauge (type FLG-02-11, TML, Tokyo Sokki Kenkyujo Co., Ltd) was glued onto the exposed lateral bone surfaces of the intact tibiae at 25 per cent of the tibia length.…”
Section: Quantification Of Peri-implant Bone Strainsmentioning
confidence: 99%
“…Recent studies of bone biomechanics found that bone failure by fracture was driven by deformation, and strain-based criteria can well predict fracture sites. [12][13][14] These findings may cause us to reconsider the use of stress-based criteria in evaluating the mechanical environment around implants and expose the need in the dental literature for validated stress and strain criteria for predicting OMI or dental implant failure in finite element (FE) models.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,23 Finite element models obtained from micro-CT scanning have been widely used for the evaluation of biomechanical features of oral tissues and biomaterials. 15,24 The micro-CT scanning allows for voxel-based finite element models to reproduce with high fidelity the external geometry and the internal architecture of the bone tissue and biomaterials. 15 Regarding mathematical analysis by the FE method, any technique used for modeling has more reliability when the results are compared with experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] It is known for long that for biologic or artificial materials (such as implants) interfacing biologic tissues, the success is limited because of complex structure of biologic materials or the interface. 15 There, however, are few studies concerning the specific situation of the deformation around a single implant.…”
mentioning
confidence: 99%